Mortality Attributable to Low Levels of Education in the United States - Krueger, Patrick M.; Tran, Melanie K.; Hummer, Robert A.; Chang, Virginia W. (PLOS ONE, 2015)
Background Educational disparities in U.S. adult mortality are large and have widened across birth cohorts. We consider three policy relevant scenarios and estimate the mortality attributable to: (1) individuals having less than a high school degree rather than a high school degree, (2) individuals having some college rather than a baccalaureate degree, and (3) individuals having anything less than a baccalaureate degree rather than a baccalaureate degree, using educational disparities specific to the 1925, 1935, and 1945 cohorts. Methods We use the National Health Interview Survey data (1986–2004) linked to prospective mortality through 2006 (N=1,008,949), and discrete-time survival models, to estimate education- and cohort-specific mortality rates. We use those mortality rates and data on the 2010 U.S. population from the American Community Survey, to calculate annual attributable mortality estimates. Results If adults aged 25–85 in the 2010 U.S. population experienced the educational disparities in mortality observed in the 1945 cohort, 145,243 deaths could be attributed to individuals having less than a high school degree rather than a high school degree, 110,068 deaths could be attributed to individuals having some college rather than a baccalaureate degree, and 554,525 deaths could be attributed to individuals having anything less than a baccalaureate degree rather than a baccalaureate degree. Widening educational disparities between the 1925 and 1945 cohorts result in a doubling of attributable mortality. Mortality attributable to having less than a high school degree is proportionally similar among women and men and among non-Hispanic blacks and whites, and is greater for cardiovascular disease than for cancer. Conclusions Mortality attributable to low education is comparable in magnitude to mortality attributable to individuals being current rather than former smokers. Existing research suggests that a substantial part of the association between education and mortality is causal. Thus, policies that increase education could significantly reduce adult mortality.